Modeling Secondary Organic Aerosols in China: State of the Art and Perspectives - Li, Jingyi; Zhang, Haowen; Li, Lin; Ye, Fei; Wang, Hongli; Guo, Song; Zhang, Na; Qin, Momei; Hu, Jianlin (Current pollution reports, 2023)
Purpose of Review Fine particulate matter (PM 2.5 ) is a huge environmental challenge in China. Based on field studies, secondary organic aerosols (SOA) contribute greatly to PM 2.5 formation in many locations. Modeling SOA is a frontier research field in air quality and a rapidly developing field internationally. This review intends to provide a state-of-the-art understanding of the current status of SOA modeling in China and recommendations for future research. Recent Findings SOA has been shown to exhibit significant spatial and seasonal variations in China. The traditional pathway of SOA from the condensation of semi-volatile products by the oxidation of volatile organic compounds (VOCs) tends to significantly underestimate the observations. This gap has been greatly improved by considering new pathways such as the heterogeneous reactions of dicarbonyls and epoxides, the aging of primary organic aerosols and SOA, the oxidation of semi- and intermediate VOCs from emissions, and the aqueous-phase reactions of water-soluble organic species. In addition to these mechanisms, the contributions of specific precursors and sources also depend on the emission inventory of precursors, which has significant uncertainties. The interactions between anthropogenic and biogenic sources and meteorological facteros affect SOA formation. Overall, SOA plays an essential role in the budget of solar radiative forcing and the new particle formation. Summary This review focuses on the advances in modeling SOA in China since 2000. Parameterization of SOA mechanisms and properties and the emission and meteorology inputs should be improved to understand the characteristics and influences of SOA in China.